Place, Survivance, and White Remembrance: A Decolonizing Challenge to Rural Education in Mobile Modernity - David A. Greenwood (Journal of Research in Rural Education, 2009)
Michael Corbett's writing on the irony of schooling in rural places inspires me to reconsider how place shapes my commitments and my learning as a White, educated class, land- and place-attached American male. In a time of climate change, economic collapse, and other related cultural and ecological crises, our assumptions about education and schooling need to be profoundly reexamined. In Learning to Leave (2007) and in "Rural Schooling in Mobile Modernity: Returning to the Places I've Been" (2009), Corbett evokes the failures and inadequacies of contemporary schooling in rural places, developing a deep analysis of the relationship between schooling and the larger disembedding culture of global capitalism (Giddens, 1990) in which rural people and places are exploited and undervalued. Such an analysis could be extended beyond the rural scene to also include the institutionalization of education as schooling most anywhere. The irony of schooling everywhere is that it provides a questionable education for everyone; everywhere schooling functions as an engine of questionable progress.